Long-Duration Soil Heating Resulting from Forest Floor Duff Smoldering in Longleaf Pine Ecosystems - Kreye, Jesse K; Varner, J Morgan; Kobziar, Leda N (Forest science, 2020)
Abstract Prescribed fire is commonly used in southeastern US forests and is being more widely applied in fire-prone ecosystems elsewhere. Research on direct effects of burning has focused on aboveground impacts to plants with less attention to belowground effects. We measured soil heating during experimental burns in longleaf pine sandhill and flatwoods ecosystems in the southeastern US. Soil heating was minimal in frequently burned sites. Where fire had been excluded for several decades, however, we detected substantial soil heating sustained for considerable durations. Long-duration heating was most prominent where accumulated forest floor duff (Oe and Oa organic horizons) was deepest, particularly at the base of mature pines in long-unburned sites. Temperatures potentially lethal to plant tissues (≥60°C) were sustained for several hours as deep as 10 cm near pines in flatwoods sites. Sustained temperatures ≥300°C, when impacts to soil nutrients can occur, were observed for up to 35 min at mineral soil surfaces. Patterns of heating were similar in long-unburned sandhill sites; however, temperatures were generally lower and durations more brief. Heat transfer resulting from smoldering in forest floor duff deserves further attention to predict mineral soil heating, forecast fire effects, and inform restoration efforts in fire-prone ecosystems.